A Comparative study of parallel programming languages : the Salishan problems - Feo, John T., 1955- (Special topics in supercomputing, 1992)
As execution speeds reach the physical limits of single cpu computers, the only hope of achieving greater computing power is with parallel systems. Researchers have proposed countless new programming languages, but their differences, similarities, strengths, weaknesses and problem domains are subtle and often not well understood. Informed comparison of parallel languages is difficult. This volume compares eight parallel programming languages based on solutions to four problems. Each chapter includes a description of the language's philosophy, semantics and syntax, and a solution to each problem. By considering solutions rather than language features or theoretical properties, the gap is bridged between the language specialists and users. Both professionals and students in the fields of computer and computational science will find the discussions helpful and understandable.